Teori Integratif dalam Komunikasi Interprofessional Education: Systematic Review - Syarifah, Syarifah; Yonaevy, Umy (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: The integrative theory argues that theories from the perspective of scientific management and human behavior are seen as failing to integrate various factors within an organization such as organizational structure, technology used, and the environment in which the organization operates. Objectives: The objective of IPE communication is to exchange ideas, opinions, and information involving two or more professions in an effort to establish interprofessional collaboration. The aim is to integrate (compare and contrast) what has been done and said by others' research. Methods: The research was conducted by analyzing open access journals. The methodology of this research is a coverage review using the Google Scholar website accessed through Publish and Perish, with Mendeley and VOS Viewer used as tools for bibliometric analysis and semantic document network visualization. It uses the Google Scholar database and and the inclusion criteria are articles accessible in full text between 2011 and 2024. Results: Collaboration in the field of interprofessional education is quite close within this group, but still centered on a small cluster. Conclusion: This indicates the potential for developing research networks outside the same circle so that research does not stagnate and can gain cross-institutional or disciplinary perspectives. Keywords: Integratif theory, IPE Communication, Systemic review